Canon 642: Record Retention and Confidentiality - Vondenberger, Victoria (Roman Replies and CLSA Advisory Opinions 2017, 2017)
As a new major superior, I am looking for current information about provincial and institute files. 1. Which files must be retained for a certain time and which must be retained forever? 2. What level of confidentiality applies to those files? A. May relatives doing family tree research have any access to such files? I. May an archivist give relatives specific information about their relative? II. If so, what information may be disclosed? B. May the member read his/her own file? 3. In there has been a penal process which is under Pontifical Secret, may anyone have access to that file? May a new major superior have access and/or new institute council members?